2018
DOI: 10.1038/s41419-017-0222-1
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells over-expressing cxcl12 enhance the radioresistance of the small intestine

Abstract: The chemokine C–X–C motif chemokine 12 (CXCL12) greatly impacts various biological processes in mammals, including cell survival, growth and migration. Mesenchymal stem cells (MSCs) are promising tools for carrying foreign genes to treat radiation-induced injuries in the intestinal epithelium. In this study, human adipose-derived MSCs were constructed to over-express the mouse cxcl12 gene to treat such injuries. In vitro, because of the high levels of mouse CXCL12 in conditioned medium produced by mouse cxcl12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 50 publications
(63 reference statements)
1
21
0
Order By: Relevance
“…20,21,70 Our lab and others have shown that irradiation causes an elevation of CXCL12 in the BM niche. [46][47][48] Here, we also observed reduced posttransplantation engraftment into irradiated CXCL12+ hosts ( Figure 4D and supplemental online Figure 3C). Hence, we hypothesized that overexpression of Cxcl12 provides protection to the host cells upon irradiation stress, thereby increasing the competition between the host and donor cells post-transplantation.…”
Section: Overexpression Of Cxcl12 Protects Hspcs Against Irradiatiomentioning
confidence: 51%
See 1 more Smart Citation
“…20,21,70 Our lab and others have shown that irradiation causes an elevation of CXCL12 in the BM niche. [46][47][48] Here, we also observed reduced posttransplantation engraftment into irradiated CXCL12+ hosts ( Figure 4D and supplemental online Figure 3C). Hence, we hypothesized that overexpression of Cxcl12 provides protection to the host cells upon irradiation stress, thereby increasing the competition between the host and donor cells post-transplantation.…”
Section: Overexpression Of Cxcl12 Protects Hspcs Against Irradiatiomentioning
confidence: 51%
“…44 CXCL12 expression is increased upon irradiation in mice and zebrafish. [45][46][47][48] While loss-offunction and in vitro studies have shown that CXCL12 promotes quiescence of HSCs, it has also been demonstrated that CXCL12 improves the homing of HSCs to the BM in a transplantation setting. 6,[49][50][51] The aim of this study was to test the effects of elevated Cxcl12 levels in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Radiation also induces stromal production and secretion of TGF‐β in the TME, 54,55 and targeted inhibition of TGF‐β has been shown to confer radiosensitivity in breast and glioblastoma tumor models 35 . Other CAF‐secreted soluble factors including insulin‐like growth factor 2, PDGF, and CXCL‐12 have been implicated as mediators in overcoming radiation‐induced cell death 37,56,57 . The increased desmoplasia in response to RT also results in the development of chemoresistant tumors 47 .…”
Section: Rt‐induced Caf Growth Secretion Confers Radioresistancementioning
confidence: 99%
“…Elevated CXCL12 has been linked to tumor progression, along with increasing resistance to radiation and chemotherapy, and to immune suppression driven by the tumor microenvironment (Duda et al, 2011;Liu et al, 2014;Zboralski et al, 2017). Our lab and others have shown that irradiation causes an elevation of CXCL12 in the BM niche (Chang et al, 2009(Chang et al, , 2018Smith-Berdan et al, 2012). Here, we also observed reduced post-transplantation engraftment into irradiated CXCL12+ hosts ( Figure 4D and S3C).…”
Section: Overexpression Of Cxcl12 Protects Hspcs Against Irradiation mentioning
confidence: 91%